E-Module Based on Flip PDF Corporate of Integer Materials to Improve Mathematics Learning Outcomes Elementary School - Sunaryo; Sri Utaminingsih; Fitri Budi Suryani; Sumaji (Institut Agama Islam Ma'arif NU (IAIMNU) Metro Lampung, 2022)
The aims of this study were (1) to find out the feasibility of the module with Flip PDF Corporate on integers for class VI SD students in class VI SD, (2) to find out the practicality of modules with Flip PDF Corporate on integers for class VI SD students in class VI SD and (3) find out the effectiveness of the module with Flip PDF Corporate on integer grade VI SD students in grade VI SD. This type of research uses a development research model known as R&D (Research and Development) using Sugiyono's development model with the following steps: (1) potential and problems; (2) data collection; (3) product design; (4) design validation; (5) design revisions; (6) product trials; (7) product revisions; (8) trial use. The subjects in this study were students of class VI at SDN Tlogorejo 2 and students of class VI at SDN Sidomulyo 2, Wonosalam District, Demak Regency. We collected data using observation, interviews, questionnaires, and tests. The data analysis technique in this study was to find the average rating of all validators, find the average student response to the module and test the independent sample t test. The results showed that 1) the e-module using flip PDF corporate in mathematics learning integer material is feasible to use, (2) the response of teachers and students gives a positive response to the use of the e-module flip PDF corporate based and (3) the application of flip PDF corporate based on the experimental class gave better learning outcomes than the control class.